Defense and Recognition in the Climate Crisis How to Communicate About Truths, Facts and Opinions - Strohschein, Barbara (Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
XI, 335 p. 3 illus., 2 illus. in color.